Analiza porównawcza metod oceny ryzyka kredytowego - Wójciak, Mirosław; Wójcicka, Aleksandra (Comparative analysis of credit risk assessment methods, 2006)
This paper presents the results of classification of quoted companies on the basis of credit risk level. A classic method based on a synthetic measure of credit risk (SMRK) which reflects economical and financial condition of a company was used as well as a new approach of credit risk evaluation - Moody’s KMV (based on option pricing model). Forecasting abilities of both models were compared and levels of SMRK were combined with levels of probability of default (PD) which enabled such a generalization of MKMV model so that it could be used for unquoted companies. Results show that the model using SMRK reacts to changes of credit risk level of particular companies in the same time interval as Moody’s KMV model. Groups of indices that reflect risk levels in the best way and allow comparing SMRK levels with PD were selected.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 581-592